Gerakan Dakwah sebagai Sistem Kaderisasi Partai Keadilan Sejahtera - Tunjungsari, Arima Ratih; Lestari, Puji; Sumarno, Sumarno (Unnes Political Science Journal, 2017)
All of political parties need cadre recruitment processes to continue the regeneration leadership of their party, each member of candidate cadre have to follow selection to be the cadre. After the candidate cadre passes the selection, those members have to follow regeneration process which is done by politic party on implementation function of political education. By that cadre system, the leader or manager party has assessment about cadres which eventually it will be recommended to be candidate who represent their party on government positions. The research method applied in this study is descriptive qualitative. The data source consists of primary data and secondary data. The techniques of collecting data are interviewing, observation and documentation. The writer uses triangulation technique to prove the validity of the data. Data analysis can be illustrated into some steps, there are collecting data, reduction data, presentation data, and drawing conclusion or verification. The research shows that Partai Keadilan Sejahtera is political party which declares that their selves as daâwah party, it is also applied on the regeneration process. Partai Keadilan Sejahtera (PKS) is religious, the implementation of their cadre is done by some activities which usually related with the party, there are using some coaching, recitation, routine taâlim, champing, seminar, dauroh and the other meeting. Regeneration process of PKS party is done officially by leadership of the party from twig until center, this formal recruitment process constitutes the tool of cadre founding and ladder to them who will implicate on distribution character and structural position in PKS. Coaching which is done by PKS uses steps by steps or hierarchy, there are first taârif is introduction process. Second, taqwin is character development and Muslim lesson internalization. Third, tanfidz is the steps of daâwah work realization. Output is hoped from that tarbiyah movement is the cadre has daâwah skill with capacity adequately will emerge.